Chemical Denitrification with Mg0 Particles in Column Systems - Alessio Siciliano (Sustainability, 2020)
The removal of nitrate from aqueous environments through zero-valent metallic elements is an attractive technique that has gained increasing interest in recent years. In comparison to other metallic elements, zero-valent magnesium (ZVM) has numerous beneficial aspects. Nevertheless, the use of Mg0 particles for nitrate reduction in column systems has not been investigated yet. To overcome the lack of research, in the present study, a wide experimental activity was carried out to develop a chemical denitrification process through ZVM in batch column equipment. Several tests were executed to evaluate the effects of recirculation hydraulic velocity, pH, Mg0 amount, N-NO3− initial concentration and temperature on the process performance. The results show that the process efficiency is positively influenced by the recirculation velocity increase. In particular, the optimal condition was detected with a value of 1 m/min. The process pH was identified as the main operating parameter. At pH 3, abatements higher than 86.6% were reached for every initial nitrate concentration tested. In these conditions, nitrogen gas was detected as the main reaction product. The pH increase up to values of 5 and 7 caused a drastic denitrification decline with observed efficiencies below 26%. At pH 3, the ratio (RMN) between Mg0 and initial nitrate amount also plays a key role in the treatment performance. A characteristic value of about RMN = 0.333 gMg0/mgN-NO3− was found with which it is possible to reach the maximum reaction rate. Unexpectedly, the process was negatively affected by the increase in temperature from 20 to 40 °C. At 20 °C, the material showed satisfactory denitrification efficiencies in subsequent reuse cycles. With the optimal RMN ratio, removals up to 90% were detected by reusing the reactive material three times. By means of a kinetic analysis, a mathematical law able to describe the nitrate abatement curves was defined. Moreover, the relation between the observed kinetic constant and the operating parameters was recognized. Finally, the reaction pathways were proposed and the corrosion reaction products formed during the treatment were identified.